TGFU and motor coordination: the effects of a teaching program on tactical-technical performance in handball - Mazzardo, Tatiane; Monteiro, Gabriella Nelli; Silva, Willian José Bordin da; Araújo, Nayanne Dias; Silva, Schelyne Ribas da; Aburachid, Layla Maria Campos (Journal of Physical Education (Maringá), 2020)
The study was performed aiming to categorize the class sessions through TGfU and TGfU+CM to determine the effectiveness of the teaching models application and analyze the changes on handball students tactical-technical performance after the teaching program. The sample is constituted by 43 subjects (14,3±0,46) separated in two groups (G1 - TGfU e G2 – TGfU+CM), both which received teaching units with 20 class sessions of the same time duration. The categorizing of the classes granted reliability to the teaching programs applied and after the TGfU intervention only male subjects showed better performance during the game in both groups, indicating high Effect Size for group 2 (0,610) and average effect size for group 1 (0,487). Regarding the analysis between groups, there were no statistically significant differences post intervention in any of the study variables. It stands concluded that it was possible to verify, through the adherence test, that the applied teaching programs were similar in both groups, differing only the motor coordination matter input for G2, and that the teaching program was able to cause significant improvement for the male gender subjects considering the time effect for the tactical-technical performance.